2y-3=1.2-y

Simple and best practice solution for 2y-3=1.2-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-3=1.2-y equation:


Simplifying
2y + -3 = 1.2 + -1y

Reorder the terms:
-3 + 2y = 1.2 + -1y

Solving
-3 + 2y = 1.2 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
-3 + 2y + y = 1.2 + -1y + y

Combine like terms: 2y + y = 3y
-3 + 3y = 1.2 + -1y + y

Combine like terms: -1y + y = 0
-3 + 3y = 1.2 + 0
-3 + 3y = 1.2

Add '3' to each side of the equation.
-3 + 3 + 3y = 1.2 + 3

Combine like terms: -3 + 3 = 0
0 + 3y = 1.2 + 3
3y = 1.2 + 3

Combine like terms: 1.2 + 3 = 4.2
3y = 4.2

Divide each side by '3'.
y = 1.4

Simplifying
y = 1.4

See similar equations:

| 252=18n | | 5x+6x^2=5 | | (x+3i)(x+3i)= | | 5ln(x+3)=10 | | (x-y)dx+(x+y)dy=0 | | r/5=12/5 | | 9n+11=41-6n | | 4(x+2)-7=2x+2(2+x) | | 13=n/16 | | 38-18=4(x-2) | | -13=m+5 | | (-9a^7-4b)+-3a^7= | | 6x+11=2x+99 | | 2sinx-tanz=0 | | r/14=11 | | 4ln(y)= | | (4-3x^2)^(1/2) | | x-16=-33 | | y=-2(x-1.2)(-3) | | -360=20r | | y=-2(x-1.2) | | 30=10x+8 | | 35000.00+1680.00c=175000.00+550.00c | | -14=n/17 | | 10+4x+4[2x+(3-x)]=5+2[5+(x-2)] | | 2w+3+X= | | p/5=13/5 | | -12=r-10 | | 20/2(5x5)= | | 8p=5(8p+7) | | 17-2p=-83 | | 6n+5=25-4n |

Equations solver categories